Prime Minister Atal Behari Vajpayee selected speeches - Vajpayee, Atal Behari (New Delhi India. M/o Information and Broadcasting. Publication Division, 2000)
These volumes contains the selected speeches of Prime minister Atal Bihari Vajpayee from March 1998 to March 2000. The speeches are on a wide variety of subjects ranging from national affairs, economic development and science and technology to social welf
Contents: v.2. April 1999 to March 2000- v.2. March 1998 to March 1999
Keywords: Vajpayee, Atal Behari-Oratory; Speeches, addresses, etc; Festschriften